(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: This study examines the perceived advertising value of customers associated with social media advertisements disseminated by automotive companies in Kathmandu valley. In the context of the Nepalese automobile market, automotive companies engage and interact with their existing and potential customers on different social media platforms. However, there is a marketing research gap in understanding the advertising value customers associate withsocial media advertisements. Objective: This research paper aims to examine factors that influence perceived advertising value for both existing and potential customers of automotive companies associated with andexpect from social media advertisements disseminated by automotive companies. Methods: The final sample of this study consists of 120 customers existing and potential (N=120) automotive companies forboth new and reconditioned vehicles in Kathmandu Valley. Besides, in this study, cross-sectional quantitative research design and descriptive and inferential statistics have been used to report data analysis and findings. Results: The findings of this study indicate that information, credibility, and entertainment, have a significant influence on advertising value customers associate with and expect in social media advertisements of automotive companies in Kathmandu valley Implication: The study concludes that enhancement in information, credibility, and entertainment also enhances the perceived advertising value of automobile customers. Therefore, as marketing research, this study recommends automobile dealer agencies in Kathmandu valley integrate entertainment, credibility, and information elements when developing content for their social media advertisements.To fulfill customer expectations, social media advertising needs to include content that is rich in information, appears, and comes across as credible to customers with entertaining elements that positively engagethe audience.